CIFOR - a newcomer to CGIAR - Persson, R. (1999)
The process by which CIFOR became the 16th and newest research centre of the Consultative Group on Agricultural Research (CGIAR) in 1993 is described. CIFOR is located at Bogor in Indonesia and employs about 40 internationally recruited scientists including foresters, social scientists and economists. Multi-disciplinary and inter-disciplinary research is a hallmark of CIFOR's program. Its mission and research agenda are described. There are 6 core research projects: (1) causes of deforestation, forest degradation and changes in human welfare; (2) multiple resource management of natural resources; (3) plantation forestry on degraded or low potential sites; (4) conservation of biodiversity and genetic resources; (5) sustainable use and development of forest products by forest-dependent communities; and (6) local people, devolution and adaptive co-management of forests. Currently a major problem with forestry research in general is that the results are often not being used. Much of the research may be too 'academic' and research must become more problem-orientated. Another problem is priority setting and funding in forestry research. Donors have often invested heavily in the latest crisis or panacea and many assumptions behind these were wrong or at least only partially true. CIFOR needs to question the conventional wisdom, despite the difficulty in getting project funding for such an outcome. Forestry research will have an important role to play if there is a commitment to using the results. There must also be a strong commitment to doing something to reduce poverty, as it is often difficult to improve the forests if the well being of humans who depend on them is not improved. Setting priorities, using results, building capacity, involving stakeholders and so on indicates major changes occurring in forestry and forestry research. We appear to be in the middle of a paradigm shift in both forestry and forest research and CIFOR must be in the forefront of the new and challenging work arising from this shift.